POTENSI WORK-RELATED MUSCULOSKELETAL DISORDERS (MSDs) PADA POLI BERSALIN GENERAL HOSPITAL OF WEST NUSA TENGGARA PROVINCE - Bayu Prastowo; Thesa Ramadhani Iskandar; Baiq Hifzatul Puspa Mandalika; Arys Hasta Baruna (Universitas Tadulako, 2023)
The projected number of women giving birth every year is predicted to increase. However, it is not matched by birth attendants in all health care facilities. The equal distribution of the two is 1:25. This will increase the workload of midwifery services. Ergonomically supporting facilities determine the process of midwifery services. The supporting elements include effective, comfortable, safe, healthy, and efficient (ENASE) to prevent the potential for musculoskeletal disorders (MSDs). This research was conducted on midwifery employees at the Maternity Poly VK Teratai Regional General Hospital in West Nusa Tenggara Province. The parameters for measuring the potential of MSDs used a standard Nordic body map questionnaire (SNQ). SNQ mapping generally complains about MSDs in the moderate risk category and does not limit productivity, so preventive action is needed in the future. Long-term priority preventive and monitoring needs to be done in the neck region. Meanwhile, the main problem is facilities that do not meet the concept of the ENASE workstation.